Ferromagnetism and Half‐Metallicity in Atomically Thin Holey Nitrogenated Graphene Based Systems - Choudhuri, Indrani; Pathak, Biswarup (Chemphyschem, 2017)
Metal‐free half‐metallicity has been the subject of immense research focus in the field of spintronic devices. By using density functional theoretical (DFT) calculations, atomically thin holey nitrogenated graphene (C2N) based systems are studied for possible spintronic applications. Ferromagnetism is observed in all the C‐doped holey nitrogenated graphene. Interestingly, the holey nitrogenated graphene (C2N) based system shows strong half‐metallicity with a Curie temperature of approximately 297 K when a particular C‐doping concentration is reached. It shows a strong half‐metallicity compared with any metal‐free systems studied to date. Thus, such carbon nitride based systems can be used for a 100 % spin polarized current. Furthermore, such C‐doped systems show excellent dynamical, thermal, and mechanical properties. Thus, we predict a metal‐free planar ferromagnetic half‐metallic holey nitrogenated graphene based system for room‐temperature spintronic devices. Holey doped graphene: By using density functional theoretical (DFT) calculations, C‐doped holey nitrogenated graphene based systems were studied for possible spintronic devices. Ferromagnetism is observed in all C‐doped systems and strong half‐metallicity is observed after achieving a particular C‐doping concentration (16.67 %) in C2N. The presence of half‐metallicity can be explained by the unsaturation on the doped C atom.